A Comparative Legal Analysis of Insolvency (Bankruptcy) of Individuals Under Uzbekistan and Foreign Legislation (Texas Journal of Multidisciplinary Studies, 2023)
The article provides an in-depth examination of the laws and regulations governing the insolvency or bankruptcy process for individuals in Uzbekistan, comparing them to the corresponding laws in other jurisdictions. The author delves into the legal framework surrounding individual insolvency within Uzbekistan, highlighting the key provisions, procedures, and rights available to debtors and creditors in such cases. Additionally, the article presents a thorough comparative analysis of relevant foreign legislation from various jurisdictions, allowing readers to gain a comprehensive understanding of how insolvency proceedings differ across different legal systems.